Penanaman Nilai-Nilai Pendidikan Karakter Siswa Melalui Kegiatan Keagamaan dan Non Keagamaan di Madrasah - Ubaidillah, Ubaidillah; Edison, Alvira Rahma; Amalina, Nur; Najjah, Safinatun; Ilmiah, Nur Hardianti; Putri, Dinda (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe the inculcation of character education values among students through religious and non-religious activities in madrasahs. The background of this study is the decline in student morality in the digital era, which demands educational institutions particularly madrasahs to play an active role in shaping students’ personalities with noble character. This research used a qualitative field study approach. Data were collected through observation, interviews, and documentation involving the head of the madrasah, teachers, and students. The findings show that religious activities such as congregational prayers, Qur’an recitation, and Islamic holiday celebrations effectively instill values of religiosity, responsibility, and discipline. Meanwhile, non-religious activities such as flag ceremonies, social activities, and community service foster values of nationalism, cooperation, and environmental care. Character implementation is achieved through teacher role modeling, habituation, and the enforcement of school rules. In conclusion, integrating religious and non-religious activities in madrasahs serves as an effective strategy for holistic character formation.